Multifunctional nanomedicine targeting the 'seed-and-soil' of hair follicles via simultaneous alleviation of oxidative stress and activation of autophagy for androgenetic alopecia therapy - Yuanzheng Chen; Qubo Zhu; Yanbin Zhou; Wenhu Zhou; Yan Chen (Materials Today Bio, 2025)
Androgenetic alopecia (AGA) is a prevalent form of hair loss, which significantly affects both aesthetics and quality of life. Hair regeneration in AGA requires the transition of hair follicles from the telogen phase to the anagen phase, alongside a healthy microenvironment, analogous to seed germination, where breaking dormancy and providing fertile soil are essential. In this context, we propose that targeting the ''seed-and-soil'' model by activating autophagy in hair follicles (seeds) and alleviating oxidative stress in the hair follicle microenvironment (soil) could be an effective strategy for AGA treatment. Through network pharmacology and cell-based experiments, we identified curcumin (Cur) as a potential agent capable of activating autophagy and alleviating oxidative stress—both critical processes for hair follicle regeneration. To facilitate biomedical application, we developed a novel nanoparticle formulation, TFC, achieved by self-assembling Cur and tannic acid with Fe3+ via metal coordination. TFC nanoparticles demonstrated excellent colloidal stability, high Cur loading capacity (52 %), and potent antioxidant properties. In vitro studies showed that TFC effectively scavenged reactive oxygen species (ROS) and activated autophagy in human dermal papilla cells, offering significant protection against oxidative stress. In an AGA mouse model, TFC delivered via microneedles accelerated hair growth, promoted hair follicle proliferation, and enhanced angiogenesis, with superior efficacy compared to minoxidil and minimal side effects. This study suggests that Cur-loaded TFC, by targeting oxidative stress and autophagy in hair follicle cells, represents a promising novel approach for AGA treatment.